Micropropagation of Juniperus navicularis, an endemic and rare species from Portugal SW coast - Castro, Mário Rui (2011)
Juniperus navicularis Gand (= J. oxycedrus L. subsp. transtagana Franco) is an endemic dioecious shrub from the Plio-Plistocene transition sands of the west Portuguese coast line. It grows in sole or mixed stands along with Pinus pinea and P. pinaster and, more rarely, with Quercus lusitanica. In order to reduce fire incidence in these Mediterranean mixed stands, forest management practices of mechanical or chemical treatments, have drastically reduced J. navicularis populations. In addition, the fast expansion of touristic areas along with a low seed germination rate further endangers this species. In this study we developed a protocol for micropropagation of adult J. navicularis. Microcuttings were obtained from lateral and apical twigs of both female and male mature plants, and used as explants. Microcuttings with axillary buds were grown on different media and plant growth regulators combinations. Developmental parameters were evaluated to define the best medium and plant growth regulator concentration for shoot bud induction during the multiplication cycles. Olive Medium and Gupta and Durzan medium, both supplemented with 0.45 µM 6-benzyl-amino-purine, were the most favourable of all combinations tested achieving more than 3 new shoots per explant. The highest rooting (60%) was obtained in microshoots cultured in Olive Medium when supplemented with indole-3-butyric acid at 12.3 µM. With this multiplication protocol, it was possible to obtain more than 500 shoots from the initial 20, after three multiplication cycles in 3 months.